PERAN MOTIVASI TERHADAP TINGKAT KOOPERATIF PASIEN YANG BERKUNJUNG KE RUMAH SAKIT GIGI DAN MULUT UNSYIAH - Herwanda Herwanda; Cut Fera Novita; Mhd Parlindungan Berutu (Dentistry Faculty, 2017)
Health is an important condition inlife and to achieve this it takes a motivation, especially the motivation to recover from a disease. Patient motivation means an impulse from within themselves that cause patient come to visit Oral and Dental Hospital (RSGM) of Syiah Kuala University. Patient motivation is influenced by several factors, which were communication between patient and young dentist and health care and the patient behavior itself. Motivation in every single patient would be a positive impact in improving patient dental cooperative or partnership in performing a treatment and maintenance procedure. Cooperative is response behavior of patient which appear by the ability or collaborative skills related to dental procedure. The high level of cooperative will make patient act positive toward dental health so that dental procedure would be more effective and efficient. The purpose of this study is to determine whether there is a role of motivation to patient cooperative who visited Oral and Dental Hospital (RSGM) of Syiah Kuala University. This study was a cross-sectional study. The sampling method was done by purposive sampling that included 67 subjects who visited Oral and Dental Hospital (RSGM) of Syiah Kuala University. This research was done by using a questionnaire that was designed by the researcher. Results of analysis using Kendall's Tau test showed a significant relationship between motivation patient on patient cooperative (p 0.05). It is concluded that there is a role of motivation on patient cooperative who visited Oral and Dental Hospital (RSGM) of Syiah Kuala University.Keywords: Motivation, Level of Cooperative, Oral and Dental Hospital (RSGM) of Syiah Kuala University